Self-Regulation in Preschool: Examining Its Factor Structure and Associations With Pre-academic Skills and Social-Emotional Competence - Korucu, Irem; Ayturk, Ezgi; Finders, Jennifer K.; Schnur, Gina; Bailey, Craig S.; Tominey, Shauna L.; Schmitt, Sara A. (Frontiers in Psychology, 2022)
Self-regulation in early childhood is an important predictor of success across a variety of indicators in life, including health, well-being, and earnings. Although conceptually self-regulation has been defined as multifaceted, previous research has not investigated whether there is conceptual and empirical overlap between the factors that comprise self-regulation or if they are distinct. In this study, using a bifactor model, we tested the shared and unique variance among self-regulation constructs and prediction to pre-academic and social-emotional skills. The sample included 932 preschool children (Mage = 48 months, SD = 6.55; 49% female), their parents, and their teachers in the United States. Children’s self-regulation was assessed using measures of executive function, behavioral self-regulation, and emotion regulation. The bifactor model demonstrated a common overarching self-regulation factor, as well as distinct executive function and emotion regulation factors. The common overarching self-regulation factor and executive function predicted children’s pre-academic (i.e., mathematics and literacy) and social-emotional skills. The emotion regulation factor predicted children’s social-emotional skills. Identifying the shared and unique aspects of self-regulation may have important implications for supporting children’s regulatory skills as well as their success in school.